A formal approach for the specification of digital complex objects - Toffoli, Ticiana O.; Kozievitch, Nádia P.; Gonçalves, Marcos A.; Torres, Ricardo da S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Complex objects (COs) have surged as a way to integrate different digital resources under a same logical unit in order to facilitate aggregation and reuse. However, there is still a lack of consensus on precise theoretical foundations for COs, especially regarding design and specification, which compromise their utility and integration with existing software tools. Moreover, there has been little investigation on aspects related to the modeling of COs by the end user, much due to the lack of appropriate tools for this goal. In this work, we present a new Digital Library (DL) metamodel specially designed for the CO modeling which is grounded in formal theoretical specification for COs. More specifically, our goal is two-fold: (i) to indirectly validate our CO formalization by instantiating it within a DL modeling tool -- 5SGraph; and (ii) to investigate the difficulties of CO modeling and specification by real users using the specified metamodel. Experiments with real users indicate that the use of the metamodel and the graphical tool facilitates the understanding of the COs structure and the modeling process.